Healthcare students attitudes opinions perceptions and perceived obstacles regarding ChatGPT in Saudi Arabia: a survey‑based cross‑sectional study - Mohammad K. Alharbi; Wajid Syed; Adnan Innab; Mahmood Basil A. Al-Rawi; Ahmed Alsadoun; Adel Bashatah (Scientific Reports, 2024)
Abstract With growing technology, it’s easier for students to accomplish their assignments with little or no effort. This study assesses attitudes, opinions, perceptions, and perceived obstacles regarding ChatGPT among healthcare students at King Saud University, Riyadh, Saudi Arabia. A cross-sectional study among healthcare students was conducted from the beginning of January to April 2024 using social media, platforms through a prevalidated series of questionnaires. This study included students from the College of Pharmacy, Nursing, and Emergency Medical Services (EMS). A total of 354 students included in the study. The data was analyzed using a statistical package for social science (SPSS). Among the healthcare students 39.8% (n = 141) of them were between 23 and 24 years old and most of them were male 68.4% (n = 242). The majority of the healthcare students 91.2% (n = 323) were familiar with the term “ChatGPT, while 75.1% (n = 266) of them were comfortable to some extent in using ChatGPT in their academic activity. Although 22% (n = 78) of healthcare students stated they had used ChatGPT in their academics 29.5% of them perceived that ChatGPT is used in information gathering. In addition, 66.7% of them showed positive attitudes towards ChatGPT. While 61.3% of the healthcare students perceived that ChatGPT may increase productivity and 84.7% of them revealed that it has a positive impact on education. The mean perceptions score of ChatGPT was significantly higher among females (22.64 ± 6.36) comparing male students (21.71 ± 4.66) (t = 1.551; p = 0.001). Similarly, the mean perception score of ChatGPT was higher among pharmacy (22.99 ± 5.48) compared to other healthcare students (F = 4.941; p = 0.008). The current findings concluded that most of the healthcare students are familiar with ChatGPT and show positive perceptions, and perceived that ChatGPT may increase productivity and have a positive impact on education. Therefore, we recommend future studies concentrate on enhancing the ethical and successful application of AI tools and ChatGPT in the academic setting is pivotal.